Perkembangan Emosi Anak Usia Dini - Citra Dwi Sekar Sari; Zusy Aryanti; Dwi Enggal Wahyuni (ALMURTAJA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Emotional development is a crucial aspect of early childhood development because it influences a child's ability to control feelings, interact socially, and adapt to their environment. Various factors, such as parenting styles, family environment, teacher roles, and learning experiences, can influence a child's emotional development. This study aims to comprehensively analyze and synthesize various previous research findings on early childhood emotional development to gain a deeper understanding of the factors that influence children's emotional development and its implications for the education and parenting process. The method used was a literature review, analyzing 30 relevant scientific articles on early childhood emotional development. Data were analyzed through a process of identifying, grouping, and synthesizing findings from various published studies. The results show that parental parenting styles are the most dominant factor in early childhood emotional development. In addition, a harmonious family environment, the role of teachers in enjoyable learning, and positive social interactions also support children's emotional development. Conversely, lack of parental attention and verbal abuse can negatively impact children's emotional development. The results also indicate that emotional development is closely related to children's social skills. Thus, early childhood emotional development requires optimal support from family and school to enable children to develop into confident, independent individuals who can interact positively with their environment.